Assessment of Contamination Risk from Fecal Matter Presence on Fruit and Mulch in the tomato fields based on generic Escherichia coli population - Topalcengiz, Zeynal; Danyluk, M.D. (Academic Press, 2022)
The purpose of this study was to evaluate the fate of generic Escherichia coli in fecal pats under different field conditions and to predict Salmonella and Shiga toxin-producing E. coli (STEC) survival dynamics based on developed models. Eight trials were conducted during spring and fall in both North and Central Florida. Fresh cattle feces (1g) was placed on mature green round tomatoes located inside (TIP) and outside (TOP) of the plant canopy. Fecal pats (10 g) were placed under (MUP) and distant (MDP) to tomato plants on plastic mulch. Pathogen populations were predicted based on developed models. Declines in generic E. coli populations over 7 days (Log CFU/g) in fecal pats were between 0.9 and 2.7 on TIP, 1.2 and 3.0 on TOP, 0.2 and 1.2 on MUP, and 0.4 and 1.5 on MDP in the Central Florida fall and spring trials, respectively. E. coli populations remained stable at ?4.2 and ? 6.5 Log CFU/g during all North Florida trials. The concentration changes in predicted Salmonella and STEC population were less than 2.1 Log CFU/g in fecal pats for all conditions. Developed models predicted similar pathogen survival trends to generic E. coli with no dramatical impact under the field conditions. © 2021 Elsevier Ltd
Keywords: Animal intrusion; Feral pig; Salmonella; Seasonality; STEC; Survival